(untitled) (Journal of Engineering, 2021)
The research investigates the term innovation and its role in elaborating architectural practice based on diffusion. The complexity of the architectural field compared with other fields shows a problem in explaining how innovations in architecture diffuse as a thought and act in a certain context of practice. Therefore, the research aims to build an intellectual model that explains the way personal thoughts resembled by unique models introduced by creative and innovator designers diffuse in a certain pattern elaborate these models into a state of prevailing thought resembled by the movement in architecture. The research will apply its model to the more comprehensive movement in architecture, which is the modern movement, for model verification and enhancement. The research concluded that innovation in architecture is about the continuity of events defining the innovator’s roles in a time pattern. With this continuity, the innovative models developed into styles and currents within a major thought elaborates, if communication tools and external factors were provided, into a "movement" leading the architectural practice framing its aesthetical and spatial preferences.